Pengembangan Game Edukasi “C-Zero Trek” sebagai Media Latihan Soal Operasi Bilangan Cacah Siswa Slow Learner SMP - Nuzula, Fauzia Firdausy; Manoy, Janet Trineke (Universitas Negeri Surabaya, 2025)
Whole number operations are an important yet challenging subject for slow learners, who tend to lose focus easily and require repeated instruction. This study aims to develop an educational game as a practice tool for whole number operations that meets the criteria of being valid, practical, and effective. The research subjects consisted of 9 slow learner junior high school students, with the object being an educational game developed using the ADDIE model. The research instruments included validation sheets, response questionnaires, observations, and tests. The research results indicate that the C-Zero Trek educational game is classified as “highly valid” based on validation results from media experts (98.33%) and subject matter experts (96.66%). Based on the student response questionnaire, the average score for the statement indicator (SIP) was 82.4%, so the game is considered “practical”. From the implementation results, it was found that 77.78% of students achieved the minimum completion level (completing at least one track or obtaining two diamonds), so the C-Zero Trek educational game also meets the “effective” criteria. Therefore, the C-Zero Trek educational game is suitable for use as an alternative, engaging, and appropriate practice question medium for students who learn slowly.